Social skills development in children aged 4–8 years - Krisztián Józsa; Tun Zaw Oo; Diana Borbélyová; Judit Podráczky (PLoS ONE, 2025)
The primary goal of this study was to examine children’s social skills (SS) development by comparing various factors (countries, genders, and age groups). Additionally, this study aimed to analyze how background variables predict the ongoing development of children’s SS. The study involved a total of 3050 Hungarian-speaking children (4–8 years of age) residing in Hungary and Slovakia. First, we investigated measurement invariance (MI) and Latent mean difference (LMD) of the SS assessment test (a part of the DIFER test – Diagnostic Systems for Assessing Development) to assess school readiness in Hungarian preschool children. The findings showed that the SS assessment test is reliable and consistent across different groups of Hungarian preschool children, as it demonstrated MI across all four levels (configural, metric, scalar, and residual) and significant LMD. It was also found that children from Hungary demonstrated superior SS when compared to their counterparts from Slovakia. Furthermore, the analysis of gender revealed that female students exhibited more advanced SS than male students. Additionally, older children displayed significantly higher levels of SS compared to younger children within their respective age groups. Although parental education emerged as a significant predictor of children’s SS development across the entire sample, distinct variations were observed when analyzing each country separately. In both countries, the gender and age of students were identified as highly significant factors contributing to their SS development. Therefore, this study carries substantial importance for educators and researchers alike, offering valuable insights into the assessment and cultivation of students’ SS development.